Breast Fibromatosis: Clinical and Pathological Insights From Two Case Reports - Vahid Soleimani; Behnaz Jahanbin; Aysan Nozheh (Clinical Case Reports, 2026)
ABSTRACT Breast fibromatosis is a benign, locally aggressive spindle‐cell tumor mimicking carcinoma. We report two cases in patients aged 15 and 61 years, highlighting its wide age range. Accurate histopathology prevents overtreatment. Modern management emphasizes individualized care, including active surveillance, complete surgical excision when needed, and long‐term follow‐up.